Analisis Implementasi Kebijakan Transfer Pricing Sebagai Prinsip Kewajaran Dan Kelaziman Dalam Transaksi Dengan Pihak Yang Mempunyai Hubungan Istimewa Pada PT Perusahaan Gas Negara Tbk - Mohamad Iman Firmansyah; Winda Wulandari (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study aims to determine the implementation of transfer pricing policies with parties that have a special relationship with PT PGN which is engaged in the transmission and distribution of natural gas. This type of research is qualitative research. Data collection techniques using observation, interviews and documentation. Data analysis techniques using data reduction, data presentation, and data verificatio n. Data obtained from library searches and interviews. Based on the research results, it shows that as a company involved in business activities, it has carried out the obligation to make transfer pricing documentation in accordance with PMK No.213/PMK.03/ 2016.